A implementação de parques eólicos e seus impactos sobre os municípios brasileiros - Sampaio, Maria Analice dos Santos (2022)
The concern with environmental issues, as well as the search for climate change mitigation, led to a race for the development and insertion of renewable energy technologies in the electric matrix of nations. Among these sources, wind energy stands out for being one of the most promising renewable sources, having an improved technology, with progressive improvement. In Brazil, wind energy plays a significant role in the country's electricity matrix, accounting for more than 9% of the Brazilian generating capacity and the second most used renewable energy. Given the relevance of wind energy in Brazil and given its high growth in recent years, this research aims to investigate the impacts of the implementation of wind farms in Brazilian municipalities. An analysis is made of the effects of the implementation of these plants on the municipal economic indicators, using a staggered differences-in-differences methodology, considering: i) several time periods; ii) variations in treatment time; and iii) dynamic treatment effects, through an Event Study project. The results showed that there are effects from the implementation of wind farms on economic indicators, such as GDP per capita and Added Value of Industry, fiscal indicators such as Tax Revenue and Tax on Goods and Services (ICMS) responded positively to the installation of wind farms when observing the estimates for the study of event. It is worth mentioning that a small increase was observed in the local labor market, represented by the per capita salary mass.